Evaluation of acute oral toxicity of Ipomoea turpethum extract loaded polymeric nanoparticles in Wistar rats - Swami, Sanskriti; Mughees, Mohd; Kauser, Sana; Wajid, Saima (Frontiers in Pharmacology, 2023)
The amalgamation of novel drug delivery techniques and potential drugs is considered the most promising tool for the treatment of diseases. In our study, we have employed N-isopropyl acrylamide, N- vinyl pyrrolidone, and acrylic acid (NIPAAM-VP-AA) copolymeric nanoparticles for delivering Ipomoea turpethum root extract. I. turpethum is a perennial herb (Convolvulaceae family) and has been used as medicine for ages. The present study was conducted to evaluate the safety of I. turpethum root extract-loaded NIPAAM-VP-AA polymeric nanoparticles (NVA-IT) in Wistar rats. An acute oral toxicity study was conducted in accordance with OECD guidelines 423 for the testing of chemicals. Different doses of NVA-IT i.e., 5mg/kg, 50mg/kg, 300mg/kg, and 2000mg/kg were administered to female Wistar rats in a stepwise manner using oral gavage. The toxicity signs were thoroughly observed for the next 14 days. At the end of the study, the blood and vital organs were harvested for hematological, biochemical, and histopathological studies. No mortality or pathological anomalies were observed even at the highest dose which exemplifies that the lethal dose would be more than 2000mg/kg body weight (GSH category 5). Behavioral changes, biochemical parameters, and histopathology of vital organs were normal after NVA-IT administration. This study demonstrated that NVA-IT nanoparticles are non-toxic and can be considered for therapeutic use in different diseases, such as inflammation, CNS diseases, Cancer, etc.